Nuclear Power Practical Aspects - Ahmed, Wael (IntechOpen, 2012)
The serious challenge facing the world today, in obtaining enough energy for growing population and in controlling the carbon emission caused by fossil fuel use, calls for nuclear energy as an alternative power source. This book presents research work and technical experience from several power plants and research institutions around the world from practical prospective. This book intends to provide useful information for scientists and those in technical fields in several areas in nuclear power plants including: nuclear systems protection, design and modelling of critical parameters in nuclear power plants, thermalhydraulic analysis, nuclear waste management and safety and reliability assessment.